2013
DOI: 10.4111/kju.2013.54.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient-Optimized Doses of Tamsulosin on Erectile Function in Men With Erectile Dysfunction and Lower Urinary Tract Symptoms

Abstract: PurposeTo investigate the relationship of improvement in erectile function (EF) with improvement in lower urinary tract symptoms (LUTS) and to assess the contribution of tamsulosin dose to the improvement of EF apart from the indirect influence of LUTS improvement in men with LUTS and erectile dysfunction (ED).Materials and MethodsFifty patients received tamsulosin 0.2 mg/d for the first 4 weeks and were subsequently divided into two groups by patient-reported outcomes. Nonescalators were maintained starting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Tamsulosin has emerged as a treatment option for BPH and LUTS owing to its different mode of action. One notable advantage of this alpha-1-blocker is to not interfere with erectile function or testosterone levels of patients ( 22 , 23 ). However, in some patients, combination therapy (with dutasteride and tamsulosin) is necessary to adequately treat BPH and LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…Tamsulosin has emerged as a treatment option for BPH and LUTS owing to its different mode of action. One notable advantage of this alpha-1-blocker is to not interfere with erectile function or testosterone levels of patients ( 22 , 23 ). However, in some patients, combination therapy (with dutasteride and tamsulosin) is necessary to adequately treat BPH and LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, changes in sexual function before and after the treatment of benign prostatic hyperplasia have attracted attention. Previous studies have reported that tamsulosin, which is used as a primary therapeutic agent for benign prostatic hyperplasia, was effective in the improvement of sexual function as well as the improvement of lower urinary tract symptoms (LUTS) [ 1 , 2 , 3 ]. However, studies on the effect of tamsulosin on ejaculation have reported that tamsulosin had inhibitory effects in the emission phase of ejaculation, including decreased ejaculatory volume [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%